SOFT TISSUE CAM IMPINGEMENT IN ADOLESCENTS: MRI REVEALS IMPINGEMENT LESIONS UNDERAPPRECIATED ON X-RAY. Issue 7 (30th July 2021) - Johnson, Benjamin L.; Alizai, Hamza; Ben, Montanez; Wagner, K. John; Youngman, Tyler; Ellis, Henry B.
Background: The presence of femoroacetabular impingement (FAI) in adolescents has been established. However, the existence of a non-ossified CAM lesion in adolescent femoracetabular impingement (FAI) is not well described. Hypthesis/Purpose: The purpose of this study is to evaluate the presence of a non-ossified or soft CAM lesion in adolescent patients with FAI. Methods: A review of a prospective cohort of patients with symptomatic FAI in an institutional registry was performed. Subjects were included if they had an MRI and lateral x-ray of the hip (45 o Dunn, Cross Table, or frog) at a baseline visit. On MRI, evaluation of the anterolateral femoral head was evaluated using radial, coronal, sagittal, or axial oblique sequences. When a soft CAM lesion was identified (all found between 2-5 o'clock), an alpha angle was performed on MRI and plain radiograph. The cohort of soft CAM lesions was reviewed and differences between radiographic and MRI alpha angles were assessed using a paired T-Test. Results: Thirty-one (9.3%) of 332 hips (mean age 16.4 yrs, range 13.66-19.59 yrs; 83.9% F) were identified with a soft impinging lesion at the femoral head-neck junction on MRI. The most common primary sport was track & field (4), the average duration of symptoms was 92.4 weeks and a majority with insidious onset (77.4%). The average alpha angle on MRI was greater than on x-ray [63.53 ± 7.94 o vs 51.25 ± 7.92 o ; p<0.05]. All subjects with soft CAM lesions demonstrated soft tissue consistent with extension of the physis (n=1), thickening of the peri-chondral ring (n=22), or thickening of the periosteum (n=8). Twenty-two of these patients (71%) with soft impingement underwent hip preservation surgery (n=13 labral repairs) with improvements in clinical outcome. Conclusion: In adolescent patients with symptomatic hip impingement, MRI may be useful to identify soft CAM lesions (non-ossified) that are under-represented on x-ray.